Earnings announcement effect on the Tunisian stock market - Ahmed Bouteska; Boutheina Regaieg (Cogent Business & Management, 2017)
This paper treats the post-earnings announcement drift. Precisely, it revisits the benefits announcement effect using various measurements of surprise unexpected earnings. In addition, this work tries to explain the persistence of post-earnings announcement drift on the financial markets using adapted methodology. The empirical study on the Tunisian stock market shows the persistence of the post-earnings announcement drift over the year 2013. It indicates that the observed post-earnings announcement drift seems to be due to the behavior of investors under psychological biases. This finding shows that the information provided by the prevision and revision of earnings forecasts is not immediately included in the price, but there is an anchoring bias in relation to the past earnings, as well as on the investor time of response to the new information provided by the market.
Keywords: 650